Analysis of The Influence of User Experience and Feature Functionality on Customers' E-Loyalty of Online Travel Service Application Traveloka - Dharmawan, Donny (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to examine how hedonic and utilitarian characteristics affect calculative commitment, flow experience, and e-loyalty. This study employs a cross-sectional design and descriptive research methodology. Customers who live in Indonesia and have utilized travel agency websites to make online hotel reservations make up the study's demographic. This study combined a judicial sampling strategy with a non-probability sampling method. There were 100 samples used in this investigation. A questionnaire was used to obtain the data. A structural equation model will be used to examine the data in this investigation. According to the analysis's findings, hedonic and utilitarian aspects enhance users' flow experiences and favourably affect their calculative commitment when utilizing travel agency services. Positive flow experiences also raise customer e-loyalty. In addition, it has been demonstrated that calculative commitment extends the degree of electronic trust. Lastly, it was discovered that e-loyalty was significantly influenced by the degree of electronic trust, suggesting that boosting customer trust in travel agencies can increase platform loyalty. Thus, strategies to strengthen hedonic and utilitarian features, ensure positive flow experiences, and build calculative commitment and e-trust may be vital to growing consumers' e-loyalty towards travel agents.